Endometrial thickness by USG as a guideline for the treatment of Dysfunctional uterine bleeding in Premenopausal Women - Charushila D. Shinde; Pankaj G. Patil; Rekha Mane (International Journal of Medical Research and Review, 2015)
Introduction: Endometrium is mucosal layer of uterus. Throughout the reproductive age, endometrium undergoes cyclical changes during each lunar month to prepare uterus for implantation. Dysfunctional uterine bleeding (DUB) is the most common cause of abnormal vaginal bleeding (AUB) during a womans reproductive years. It affects womens health both medically and socially.Aim & Objective: To decide cut of limit of Endometrial thickness (ET) by ultrasonography (USG) for the treatment of DUB patients in premenopausal women.Method: A total of 60 patients with irregular menstrual bleeding of DUB attending Department of Obstetric and Gynecology in M G M Medical College and Hospital were selected. ET was noted by USG.Result: In younger age group most of patients showed good response to medical line of treatment, while premenopausal women needed surgical line of treatment.Conclusion: ET in younger age group is in the normal range (<8mm) as compared to moderate ET (8-11mm) in perimenopausal women. In perimenopausal age, the preferred line of treatment will be either D&C or hysterectomy, when ET is >8 mm.